Effect of Debt to Asset Ratio on Return on Assets at PT. Asuransi Tugu Pratama Indonesia Tbk. 2011-2022 Period - Muhammad Saddam (Fin Sinergy: Jurnal Manajemen Keuangan, 2023)
This study aims to determine the effect of Debt to Asset Ratio on Return On Assets at PT Asuransi Tugu Pratama Indonesia Tbk for the 2011-2022 period. The method used is explanatory research. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Debt to Asset Ratio obtained an average value of 67.51%. The variable Return On Assets obtained an average value of 5.46%. Debt to Asset Ratio has a positive and significant effect on Return On Assets with a regression equation value Y = -8.350 + 0.205X, and a correlation coefficient value of 0.712 or having a strong relationship level with a determination value of 50.7%. Hypothesis test obtained a significance of 0.009 <0.05.